2020
DOI: 10.2196/preprints.22146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

System-Wide Accelerated Implementation of Telemedicine in Response to COVID-19: Mixed Methods Evaluation (Preprint)

Abstract: BACKGROUND

As the COVID-19 pandemic disrupted medical practice, telemedicine emerged as an alternative to outpatient visits. However, it is unknown how patients and physicians respond to an accelerated implementation of this model of medical care.

OBJECTIVE

To report the system-wide accelerated implementation of teleme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A pilot Telehealth Patient Satisfaction survey of approximately 150 patients selected at random from across our DayRehab® and outpatient clinics (a similar sample size to other rehabilitation-related satisfaction surveys conducted during COVID-19) [4][5][6] indicated that patients found our telerehabilitation system very easy to set up and participate in, that the video and sound quality were high, and that they were very satisfied with their experience:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot Telehealth Patient Satisfaction survey of approximately 150 patients selected at random from across our DayRehab® and outpatient clinics (a similar sample size to other rehabilitation-related satisfaction surveys conducted during COVID-19) [4][5][6] indicated that patients found our telerehabilitation system very easy to set up and participate in, that the video and sound quality were high, and that they were very satisfied with their experience:…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence generally suggests that the overall impact of telemedicine on rehabilitation services during the pandemic has been positive. [4][5][6] In this editorial, instead of summarizing expert opinions in the literature on use of telemedicine for rehabilitation services during the pandemic, we will focus on how the Shirley Ryan AbilityLab, where all the authors work, made a rapid shift across outpatient and DayRehab® programs from in-person therapy to a telerehabilitation model, using a HIPAA-compliant platform, in response to the COVID-19 pandemic in spring 2020. We discuss the process, the patients, and the benefits of our program, which we believe successfully passed the COVID test.…”
Section: The Pandemicmentioning
confidence: 99%
“…(a) Net Promoter Score (NPS): The NPS was originally developed to measure customer loyalty (Reichheld, 2003) but is also applied in hospitals (Melissant et al, 2018;Sieja et al, 2019;Garcia-Huidobro et al, 2020;Bosch et al, 2021) especially to measure satisfaction with the work environment (Legerstee, 2013;Vochin et al, 2020). The NPS measures the willingness of a person (a customer or an employee) to recommend a company, a product or working conditions to relevant others, such as family members, friends, or colleagues on a scale from 0 (very unlikely) to 10 (very likely).…”
Section: Surveysmentioning
confidence: 99%